Layer-by-layer encapsulation of Lactobacillus delbrueckii subsp. Bulgaricus using block-copolymers of poly(acrylic acid) and pluronic for safe release in gastro-intestinal conditions. (August 2017) - Quintana, G.; Simões, M.G.; Hugo, A.; Alves, P.; Ferreira, P.; Gerbino, E.; Simões, P.N.; Gómez-Zavaglia, A.
Highlights: Pluronic-acrylic acid block-copolymers were synthesized and characterized. L. bulgaricus CIDCA 333 was encapsulated with copolymers by layer-by-layer. Bacteria were plate counted after gastro-intestinal conditions simulation. Coating with 2/3 layers protected microorganisms from gastro-intestinal conditions. Coated bacteria were not toxic to eukaryotic cells and unchangeable during storage. Abstract: Lactobacillus delbrueckii subsp. bulgaricus CIDCA 333 was encapsulated by layer-by-layer (LbL) technique. Copolymers of pluronic and poly(acrylic acid), were synthesized and characterized, and chitosan was selected as cationic polyelectrolyte. The efficiency of encapsulation was evaluated by plate counting the microorganisms before and after coating, after freeze-drying with sucrose, and after exposure to simulated gastrointestinal conditions. Coated microorganisms with 2/3 layers were also protected against simulated gastro-intestinal conditions, while cultivability of uncoated bacteria significantly dropped. Confocal microscopy allowed determining the integrity and permeability of the coated and uncoated microorganisms. Coated bacteria were non-toxic to eukaryotic cells, by the MTT assay, and showed no significant decrease of cultivability before and after freeze-drying and after 60 days of storage at 4 °C. Considering the GRAS status of the used polymers, the results obtained revealed a potential delivery system of sensitive lactic acid bacteria strains in food products, ensuring their safe arrival to the gut.